Creative Thinking in Qualitative Research and Analysis - Konecki, Krzysztof T. (Qualitative Sociology Review, 2019)
I would like to present the possibility of broadening the traditional methodological and technical skills of researcher and analyst, but also the intellectual capacity of the researcher associated with combining data, categorizing, linking categories, as well as the interpretation of the causes and consequences of the emergence of certain social phenomena. Some methodologies, methods, and research techniques are more conducive to creative conceptual and interpretive solutions. Therefore, I describe the serendipity phenomenon in such methodologies as grounded theory, ethnography, phenomenological research, and contemplative inquiry. The problem of intuition in qualitative research will be also described in the paper. There will be presented also some suggestions how to be creative in qualitative research. From the review of issues of creativity in qualitative research we can derive the following conclusions: Creativity in qualitative research depends on the strength of a priori conceptualization and stiffness of the adapted methods of research and analysis. If the methodology is more flexible (as the methodology of grounded theory), the researcher can get to phenomena that he/she has not realized and which are still scantily explored in his/her field of expertise. The phenomenological and contemplative approaches allow the use of the investigator’s feelings and experience as they appear in the studied phenomena, which usually does not take place in objectifying and positivistic research. The investigator may therefore consciously use these methodologies and approaches that foster creativity. The researchers can improve their skills in thinking and creative action by doing some methodical exercises (journal writing, writing poetry as a summary of the collected data, the use of art as representation of the phenomenon, the use of meditation, observation of the body feelings, humor, etc.).